Cysteine-rich zinc finger proteins and the nuclear factor kappa-B pathway - Stoltzfus, Andrew T.; Michel, Sarah L. J. (Frontiers in Chemical Biology, 2024)
Inflammation-related disorders, such as autoimmune diseases and cancer, impose a significant global health burden. Zinc finger proteins (ZFs) are ubiquitous metalloproteins which regulate inflammation and many biological signaling pathways related to growth, development, and immune function. Numerous ZFs are involved in the nuclear factor kappa-light-chain-enhancer of activated B cells (NFκB) pathway, associating them with inflammation-related diseases that feature chronically elevated pro-inflammatory cytokines. This review highlights the predominance of ZFs in NFκB-related signaling and summarizes the breadth of functions that these proteins perform. The cysteine-specific post-translational modification (PTM) of persulfidation is also discussed in the context of these cysteine-rich ZFs, including what is known from the few available reports on the functional implications of ZF persulfidation. Persulfidation, mediated by endogenously produced hydrogen sulfide (H2S), has a recently established role in signaling inflammation. This work will summarize the known connections between ZFs and persulfidation and has the potential to inform on the development of related therapies.